RIVER ICE JAMS - A LITERATURE REVIEW. - Bolsenga, S. J. (1968)
Published information on river ice jams in many areas of the world was collected, examined, and summarized during this investigation. All manuscripts were collected and examined without regard to their apparent pertinence. The result provides a summarization of both current and historical information on the ice jam mechanism and methods of prevention and removal. Descriptions of ice jam characteristics range from mathematical to narrative treatments. Methods of prevention and removal range from dusting and thermal pollution to the more widely used blasting. Trends in the use of these techniques are indicated. The lack of success in applying prevention and removal techniques seems to be due to lack of basic information on ice jam characteristics. The results of this report can be useful in that field since a guideline for future research planning is provided. (Author)